MARRIAGE DISPENSATION FOR UNDERAGE DUE TO PREGNANCY OUT OF WEDLOCK FROM THE PERSPECTIVE OF LAW NO. 16 OF 2019 AND SHAFI'I FIQH - Thoyyibah, Wardatut (International Journal of Multidisciplinary Reseach, 2025)
This research discusses underage marriage dispensation due to out-of-wedlock pregnancy from the perspective of Law No. 16 of 2019 and Syafi'i Fiqh (Case Study in Sumber Jeruk Village, Kalisat District, Jember Regency). This research focuses on the marriage dispensation process in Sumber Jeruk village according to applicable laws and Islamic law, specifically Syafi'i jurisprudence. The researcher formulates two problems: how is the process of underage marriage dispensation due to premarital pregnancy in Sumber Jeruk village from the perspective of Law No. 16 of 2019, and what is the Syafi'i jurisprudence view on underage marriage dispensation due to premarital pregnancy in Sumber Jeruk village? The type of research used is qualitative research with a case study approach. The research results show that according to Law No. 16 of 2019, Article 7 paragraph (1), marriage is only permitted if the man and woman have reached the age of 19. Therefore, underage marriage refers to a marriage performed by a man and a woman who are both still below the minimum age limit set by law. Meanwhile, Islamic law does not specifically state the minimum age for marriage as it does in the marriage law; it only states that the requirements for marriage in Islam are being of age and of sound mind